PENINGKATAN KETERAMPILAN BERBICARA PADA PEMBELAJARAN BAHASA INDONESIA MENGGUNAKAN MODEL KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) BERBANTUAN MEDIA FLASH CARD DI KELAS IV SDN 16 PADANG BESI - Avsha, Adika; Adrias (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is based on the low speaking skills of students. This is due to: (1) Students are not accustomed to actively participating in speaking activities, (2) students' confidence in expressing their opinions is still low, (3) participation in discussions is uneven and dominated by only a few students, (4) Students have difficulty constructing sentences coherently and developing ideas in their own language, and (5) there are still limitations in the use of media as a concrete stimulus to facilitate the delivery of ideas and vocabulary mastery when speaking. The purpose of this study was to describe the improvement in speaking skills using the Two Stay Two Stray (TSTS) cooperative learning model assisted by Flash Cards in grade IV of SDN 16 Padang Besi. This study was a classroom action research (CAR) using qualitative and quantitative approaches. The subjects of this study were teachers and students in grade IV of SDN 16 Padang Besi, totaling 27 people. The results of the study showed an increase in: 1) The results of the teaching module observation in cycle I averaged 87.5% (B), increasing in cycle II to 95.83% (SB), 2) Teacher activity in cycle I averaged 89.07% (B), increasing in cycle II to 96.88% (SB), 3) Student activity in cycle I averaged 81.26% (B), increasing in cycle II to 93.75% (SB). Students' speaking skills in cycle I were an average of 77.78 (C), increasing to 87.5 (B) in cycle II. Thus, it can be concluded that the cooperative learning model of the Two Stay Two Stray (TSTS) type assisted by Flash Card media can improve speaking skills in grade IV in Elementary Schools.